Oral sedation for pain with cervical dilator placement: a randomized controlled trial - Jessica K. Lee; Anne E. Burke; Katrina Thaler; Jennifer A. Robinson; Carolyn Sufrin (Elsevier, 2021)
Objective: Assess oral sedation versus placebo for pain control with cervical dilator placement. Study design: We randomized participants presenting for dilation and evacuation to lorazepam 1 mg/oxycodone 5 mg or placebo 45 min before cervical dilator placement. Our primary outcome was median visual analog scale (VAS) pain score after dilator placement using a 100-mm VAS. We used our outcome data to calculate median pain score changes from baseline to better reflect pain score differences between study groups. Planned sample size was 30 participants per group, for a total of 60. Results: We randomized 27 participants; 9 received sedation and 11 placebo. Median pain score increase from baseline to last dilator placement was 20 [interquartile range (IQR) 8-29] and 31 (IQR 15-81) in the oral sedation and placebo groups, p = .16. Conclusion: We were unable to enroll our desired sample size, and our sample is underpowered to make any conclusions. Our results suggest that oral sedation may provide some benefit for pain relief with dilator insertion and indicate that further research might be worthwhile especially in settings that do not routinely provide these analgesics. Implications: We had difficulty with study recruitment because many patients desired oral sedation for pain management for cervical dilator placement and declined randomization. Randomized trials of pain management with a placebo arm may find recruitment challenging especially if default clinical care already includes a pain management option that patients would have to opt out of.